ASUHAN KEPERAWATAN GERONTIK DENGAN PEMBERIAN INTERVENSI JUS BUAH APEL TERHADAP PENURUNAN KADAR KOLESTROL DI PANTI WERDHA AYAH BUNDA TANGERANG TAHUN 2023 - Riska Elda Sari; Siti Robeatul Adawiyah; Siti Rahayu; Rina Puspita Sari (Nusantara Hasana Journal, 2023)
Beckground : Cholesterol is formed naturally in the body which is the basis for forming hormones that are ver necessary to regulate growth and the body’s working mechanism. Hypercholesterolemia is a condition where cholesterol levels exceed normal limits (>200 mg/dl), this condition will increase the occurrence of coronary heart disease and stroke. Consuming fruits and vegetables is one of the non-pharmacological therapies to maintain cholesterol. Apples have many beneficial ingredients for the bdy, one of which is quercetin which acts as an antioxidant to fight bad cholesterol (LDL). Purpose : The purpose of this paper is to provide an overview of nursing care for the elderly by administering apple juice interventions to reduce cholestero levels. Method : case study design using nursing care. The case study sample used 1 patient. Results : The results obtained were that before being given apple juice the results of cholesterol levels were 217 mg/dl and after beinggiven 200ml of apple juice for 7 days, taken regularly once a day after eating, the results obtained were cholesterol levels of 159 mg/dl, then there was decrease in cholesterol levels after being given apple juice to cholesterol clients. Thus, giving apple juice can effectively reduce cholesterol levels.